Silicon Mitigates the Effects of Zinc and Manganese Deficiency in Plants - Oliveira, Kamilla Silva [UNESP]; Felisberto, Guilherme; de Mello Prado, Renato [UNESP] (Springer Nature, 2023)
In this chapter, we clarify the importance of zinc and manganese for tropical crops since several conditions in these soils around the world induce plant deficiency with consequences in physiological and biochemical metabolism, leading to losses in growth and production. Thus, we initially discuss the roles of these micronutrients in plants and the results of shortages in the soil and the plants. After that, we address the most recent works in the literature focusing on zinc and manganese deficiency that have used silicon as a beneficial element to mitigate and alleviate these deficiencies. Therefore, we clarify the physiological and biochemical mechanisms described for Si to favor tropical species production even when facing the challenge of zinc and manganese shortages in metabolism.
Keywords: Antioxidant activity; Oxidative stress; Photosynthesis; Redistribution; Uptake